Adolescent school retention post COVID-19 school closures in Kenya: A mixed-methods study. - Ruth Nanjekho Wafubwa; Erica Soler-Hampejsek; Eva Muluve; Daniel Osuka; Karen Austrian (PLoS ONE)
This mixed methods study investigated factors associated with school retention among marginalized adolescents in four different settings in Kenya, following COVID-19 school closures. Logistic regressions were used to examine factors associated with school retention in 2022 among 1798 adolescent students aged 10-19 in 2020. Qualitative data from 89 in-depth interviews (64 adolescents aged 11-19 and 25 parents), and 21 key informants were thematically analysed. Among female adolescents, age (aOR = 0.76, 95% CI: 0.67, 0.87) and internet access (aOR = 0.55, 95% CI: 0.35, 0.87) were negatively associated with school retention. Engaging in income-generating activities was similarly linked to reduced school retention (aOR = 0.27, 95% CI: 0.16, 0.46). For male adolescents, household loss of income (aOR = 0.40, 95% CI: 0.21, 0.76) and engaging in income-generating activities (aOR = 0.07, 95% CI: 0.02, 0.19) were associated with lower school retention. The qualitative findings highlighted the gendered nature of barriers to school retention. Specifically, pregnancy, child marriage, and related childcare responsibilities emerged as important constraints for girls, whereas engaging in income-generating activities and drug and alcohol use were more dominant factors for boys. Across both genders, financial constraints were a key barrier to school retention. This study underscores the multifaceted nature of factors influencing school retention among marginalized adolescents in times of crisis such as the COVID-19 pandemic. The findings provide useful information for designing targeted policies and programmes for adolescent school retention in times of crisis.